Commune sepulcrum: The ‘Catullan’ Memory of Troy in Vergil’s Aeneid - Somfai, Péter (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In Roman literature, Troy appears as a locus memoriae on several occasions. As a locus memoriae is an image of a location’s past state, it inevitably recalls that past state’s absence in the present. Troy as a literary locus memoriae recalls its own present absence, that it is only a ruin, or – according to Lucan – even less than a ruin. In this context, a literary phenomenon, i. e. the depiction of Troy being the equivalent of the absence of/or the grief for the loss of something or somebody can later be traced in the Roman poetry. Catullus, mourning his brother’s death at Troy, calls the city the common grave (commune sepulcrum) of Asia and Europe in his carmen 68. Regarding Troy, several complex allusions can be noticed in Vergil’s Aeneid recalling both Catullus 68 and 101, the two poems that are in both thematic and intertextual connection with each other. The purpose of the present study is to examine – by means of analysing the above mentioned intertexts – what kind of special locus memoriae Troy becomes in the Aeneid. This will be of crucial importance to observe the way Troy later appears in Lucan’s Bellum Civile.